Design and Build Project Scheduling Applications Using the Critical Path Method - Muhammad Raihan; Abdul Syahputra Sidabalok (Bigint Computing Journal, 2025)
Effective project planning and scheduling is a crucial factor in ensuring the successful implementation of projects, especially in the construction sector. CV Kayfa Permata, a construction company, often faces challenges in managing project time and resources optimally. To overcome these challenges, this study aims to design and build a desktop/web-based project scheduling application that implements the Critical Path Method (CPM) method. The uniqueness of this application lies in its ability to automatically calculate critical paths, total project duration, as well as visualize work network diagrams, which are directly tailored to the operational needs of the local company. Different from a theoretical or simulation approach, this research produces an applicative solution that can be implemented directly in a real work environment. The application development methodology uses a waterfall approach, with stages of needs analysis, system design, implementation, and testing. The test results show that the app is able to improve the efficiency of project scheduling and simplify the decision-making process. With this application, it is hoped that the project scheduling process at CV Kayfa Permata will be more systematic, efficient, and measurable.